The Role of Analysts in Intra-Industry Information Transfer - Hilary, Gilles; Shen, Rui (The Accounting Review, 2013)
ABSTRACT When a firm issues a management forecast, analysts who have observed more forecasts from this firm since covering it (i.e., have more MF-Experience) subsequently improve their own accuracy more and provide timelier earnings forecasts for other (non-issuing) firms in the same industry. We also find that, subsequent to a management forecast, investors are more responsive to forecast revisions for non-issuing firms made by analysts with more MF-Experience. Further tests suggest that our results are not explained by endogeneity in firm coverage. Data Availability: Data are commercially available.